The Utilization of Used Stuff in Making Teaching Tool Based on Local Wisdom as a Means to Increase Teacher Professionalism - Rudi Susilo; Nur Ardiansyah; Eli Trisnowati; Desi Nurhikmahyanti (JURNAL SPEKTRA, 2021)
The aim of this study was to determine the feasibility of teaching tool based on local wisdom from used stuff to improve the professionalism of teachers in SD N 1 Potrobangsan, Magelang. This research was qualitative research. The research subjects were eight elementary schools teachers. The instrument used in this study was a questionnaire. The data analysis technique was the scale method with modified Likert scale. The product is teaching tool which contain the elements of the local wisdom and made from used stuff. The visual aids that we made were volcanic eruption simulation of Mount Merapi which made from used cardboard containing elements of the local wisdom of the Magelang. The results of the data analysis concluded that the teaching tool based on local wisdom from used stuff are suitable to be used as teaching tool as a means of increasing teacher professionalism. This can be seen from the average value of the indicator of good teaching tool of 87.14%.